Mapping Activist Responses and Policy Advocacy for Street Harassment: Current Practice and Future Directions - Fileborn, Bianca (European journal on criminal policy and research, 2022)
This article presents findings from a comprehensive mapping exercise of activist responses to, and policy advocacy for, street harassment across the US, UK and Australia. Analysis of activist groups found that the bulk of responses constituted forms of “awareness raising” and documenting the experiences of victims, suggesting that current advocacy is largely situated within the “problem identification” phase of policy development. The extent and focus of activism and advocacy efforts varied across the three locations, with the responses advocated for shaped by local concerns and politics. In particular, activist groups diverged in their support for criminal justice responses to street harassment. Where policy and other initiatives have been developed, these have rarely been evaluated, and there is a clear need to establish an evidence base to better support future policy and practice developments.